Third Culture Kids: Growing Among Worlds by David C. Pollock & Ruth E. Van Reken - Gundogdu, Hasene (Central European Journal of Educational Research, 2022)
Bibliography of the reviewed book: Pollock, D., & Reken, R. (Revised Edition 2009). Third Culture Kids: Growing Among Worlds. Nicholas Brealey Publishing.